Surgical management of the impacted dormia basket during ERCP - Tandup, Cherring; Kaman, Lileswar; Sinha, Saroj Kant (International Surgery Journal, 2019)
The incidence of associated common bile duct stones in patients undergoing cholecystectomy is 10%. The present day management of common bile duct stone is pre- or post-operative endoscopic retrograde cholangio-pancreatography and clearance of common bile duct. Complications of ERCP and CBD stone extraction have been reported to occur in 5 to 10% cases which may range from mild to life threatenin Here we report a case of cholelithiasis with choledocholithiasis with obstructive jaundice and patient while undergoing ERCP and stone retrieval had complication of impacted dormia basket which was managed by surgery.